Synthesis and Characterization of Dye-Doped Polymer Films for Non-linear Optical Applications - Mishurov, Dmytro; Voronkin, Andrii; Roshal, Alexander; Bogatyrenko, Sergiy; Vashchenko, Olga (Lviv Polytechnic National University, 2019)
In this work polymer nonlinear optical (NLO) materials in the form of thin films based on 3,7,3’,4’-tetrahydroxyflavone and diglycidyl ether of bisphenol A were obtained and investigated. It was found that the influence of the chromophore concentration on values of the macroscopic NLO susceptibilities (χ(2) of doped polymer films has extreme character. The maximum value of χ(2) is 6.11 pm/V at the concentration of dopant 20 wt %.

Одержані і досліджені полімерні нелінійно-оптичні (НЛО) матеріали на основі 3,7,3',4'-тетрагідроксифлавону і ДГЕБА у вигляді тонких плівок. Визначено, що за лежність значень макроскопічних нелінійно-оптичних сприйнятливостей (χ(2)) допованих полімерних плівок від концентрації хромофору має екстремальний характер. Максимальне значення χ(2) становить 6,11 пм/В за концентрації допанту 20 % мас.
Синтез та характеристика допованих полімерних плівок для нелінійного оптичного застосування
Keywords: polymer composite; doped epoxy polymer; chromophore; nonlinear optical susceptibility; 3,7,3’,4’- tetrahydroxyflavone; полімерні композити; доповані епоксидні полімери; хромофори; нелінійно оптичні властивості; фізетин